Comparison of Accuracy and Speed in Computer-Assisted Versus Conventional Methods for Pediatric Drug Dose Calculation: A Scenario-Based Randomized Controlled Trial. (March 2021) - Chongthavonsatit, Nichapha; Kovavinthaweewat, Chayanich; Yuksen, Chaiyaporn; Sittichanbuncha, Yuwares; Angkoontassaneeyarat, Chuenruthai; Atiksawedparit, Pongsakorn; Phattharapornjaroen, Phatthranit
Pediatric emergency care is prone to medication errors in many aspects including prescriptions, administrations, and monitoring. This study was designed to assess the effects of computer-assisted calculation on reducing error rates and time to prescription of specific emergency drugs. We conducted a randomized crossover experimental study involving emergency medicine residents and paramedics in the Department of Emergency Medicine at Ramathibodi Hospital. Participants calculated and prescribed medications using both the conventional method and a computer-assisted method. Medication names, dosages, routes of administration, and time to prescription were collected and analyzed using logistic and quantile regression analysis. Of 562 prescriptions, we found significant differences between computer-assisted calculation and the conventional method in the calculation accuracy of overall medications, pediatric advanced life support (PALS) drugs, and sedative drugs (91.17% vs 67.26%, 86.54% vs 46.15%, and 89.29% vs 57.86%, respectively, P < .001). Moreover, there were significant differences in calculation time for overall medications, PALS drugs and sedative drugs (25 vs 47 seconds, P < .001), and computer-assisted calculation significantly decreased the gap in medication errors between doctors and paramedics ( P < .001). We conclude that computer-assisted prescription calculation provides benefits over the conventional method in accuracy of all medication dosages and in time required for calculation, while enhancing the drug prescription ability of paramedics.